Impact of Visual and Aural Education on the Anxiety Level of Patients Under Spinal Anesthesia for Preoperative Caesarean Section - Anggara, Ari; Triyudono, Danang; Lintang Suryani, Roro (Java Nursing Journal, 2024)
Background: The implementation of Sectio Caesarea (SC) requires anesthesia to relieve pain in patients who will undergo surgical procedures. SC action can cause anxiety in pregnant women who will undergo surgery. Purpose: Knowing the effect of audiovisual education on the anxiety level of preoperative ectio caesarea patients with spinal anesthesia at RSUD dr. H. Soemarno Sosroatmodjo Tanjung Selor. Method: This research design uses a pre-experimental design with a Pre and post-test without control approach. Accidental sampling technique. The number of samples obtained was 40 respondents. Measurement of anxiety using the Amsterdam Preoperative Anxiety and Information Scale (APAIS) with audio visual education intervention. Findings: The age of the patients was mostly in the category of 20-35 years, 35 patients (87.5%) and the majority of parity with primiparous 24 patients (60%), Anxiety of preoperative cesarean section patients before giving audio visual education about cesarean section surgery with spinal anesthesia the majority with moderate anxiety 25 patients (62.5%), Anxiety of preoperative cesarean section patients after giving audio visual education about cesarean section surgery with spinal anesthesia the majority with not anxious or normal a total of 21 (52.5%). Conclusion: There is an effect of audio-visual education on the anxiety level of preoperative sectio caesarea patients with spinal anesthesia at RSUD dr. H. Soemarno Sosroatmodjo Tanjung.